TOWARDS THE USE OF THE FIRST LANGUAGE IN EFL TEACHING: THE STUDENTS’ PERSPECTIVE - Purtseladze, Valeria (Online Journal of Humanities ETAGTSU, 2022)
The paper discusses the issue of using the first language, as well as the importance of the grammar-translation method in teaching English as a foreign language to multilingual groups in higher educational institutions from the standpoint of students’ perception of the problems in question. The empirical data comprise the results of the recent survey conducted among the BA students of Ivane Javakhishvili Tbilisi State University. The study focuses on the following points: 1. The necessity of using the first language in EFL teaching; 2. The main problems concerning the use of the first language in multilingual EFL classrooms; 3. The importance of the grammar-translation method in EFL teaching. The study demonstrates that the use of the first language is of exceptional importance for the efficiency of the educational process in EFL classrooms. However, the findings also show that the first language should primarily be used for explanatory or interpretative purposes, rather than constitute a basic means of communication in the classroom. According to the survey, the grammar-translation method, which has recently been a matter of controversy among language teachers, is still perceived as a useful technique for learning a foreign language by the majority of the respondents. The study represents a supplement to the existing findings and enables us to once again see the problems in question from the students’ perspective. The findings of the given research were partially presented and discussed at the fourth international conference “Second Language Teaching/Acquisition in the Context of Multilingual Education”, 29 - 30 September 2021. Full Text (PDF)